Internalized homophobia and depression in lesbian women: The protective role of pride. Issue 3 (3rd July 2018) - Rubino, Constance; Case, Rosalind; Anderson, Alastair
Abstract: This study sought to examine the association between internalized homophobia and depressive symptoms in lesbian women, and establish whether such a relationship was mediated by collective self-esteem, self-esteem, and self-disclosure. Participants were 225 self-identified lesbian women in the community. Structural equation modeling was used to demonstrate that an underlying construct, labeled pride, reflected participants' levels of self-esteem, collective self-esteem, and self-disclosure. Internalized homophobia was moderately and negatively predictive of pride, and pride was strongly and negatively predictive of depression. Results highlight the potentially protective role of pride in the prevention of depression among lesbian women.